BIMBINGAN KONSELING BELAJAR - Kaminudin Telaumbanua; Abraham Laia; Yonatan Putra Ndruru; Sonitema Gulo; Baziduhu Ndruru; Siapatau Wau; Murulina Zebua; Rut Trinitatis Waoma; Munida Giawa; Jornius Hulu; Resta Soraya Gaurifa; Rimi Rosalia Dachi; et al. (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this service activity is to guide students in carrying out teaching practices at school. The method of service activities is carried out by interviews and direct practice. The results of the service activities showed that the activities carried out were able to encourage and motivate the participants in building students' self-confidence in carrying out practice in carrying out guidance related to problems faced both in personal problems and problems in learning as well as the ongoing lecture process. The conclusion is that the guidance activities carried out are able to encourage and motivate students in carrying out group and individual guidance in learning.